BLOWDOWN BOILER MASS FLOW SIMULATION IN MAINTAINING RELIABILITY AND EFFICIENCY OF COAL FIRED STEAM POWER PLANT (CASE STUDY IN PLTU OMBILIN 2 X 100 MW) - Sefriadi, Odi
The concentration of impurities in the steam drum boiler is an important factor that must be maintained to maintain the reliabilityof the power plant. One of the efforts made is to blowdown. Boiler blowdown is carried out to drain water out of the steam drum. Mass flow rate and duration of blowdown must be set precisely because if it is excessive it will reduce the efficiency of the power plant, otherwise if it is deficient it will increase the concentration of impurities in the boiler. To find out the mass flow rate and the exact blowdown duration, simulations are carried out using approaches of numerical equations. The simulation is done using 3 scenarios. The first scenario, the simulation is done to reduce the concentration of silica in the steam drum that has exceeded the safe limit. The second scenario, the simulation is carried out to prevent the silica concentration in the steam drum from exceeding its safe limit. The third scenario,the simulation is carried out to overcome the condenser leak. The case study in this research was conducted at the Ombilin power plant, which strengthens the electricity system on the island of Sumatra, Indonesia. The regulation of the blowdown mass flow rate at the Ombilin power plant is done every 4 hours following a chemical analysis schedule in the laboratory. All scenarios in this research were carried out by comparing the simulation of blowdown setting according to the actual procedure at the Ombilin power plant to the optimum simulation results of blowdown settings. In the first scenario, the potential for energy savings for 4 hours is 71,011,836.9 kJ. In the second scenario, it is known that the silica concentration in the steam drum can be kept under safe limits even though the silica concentration in the feedwater boiler system increases. In the third scenario, we obtain the mass flow rate and the exact timing of the blowdown adjustment in controlling the condenser leak.